Magmatism of the submarine Vityaz Ridge (Pacific slope of the Kuril Island Arc). - Lelikov, Evgeny P; Emelyanova, T A; Baranov, Boris V (PANGAEA, 2008)
Original results of igneous rock studies are presented. The rocks were dredged during a marine expedition (cruise 37 of R/V Akademik M.A. Lavrent'ev in August-September, 2005) in the region of the submarine Vityaz Ridge and the Kuril Arc outer slope. Several age complexes (Late Cretaceous, Eocene, Late Oligocene, Miocene, and Pliocene-Pleistocene) are recognizable on the Vityaz Ridge. These complexes are characterized by a number of common geochemical features since all of them represent formations of island arc calc-alkali series. At the same time, they also have individual features reflecting different geodynamic settings. The outer slope of the Kuril Arc demonstrates submarine volcanism. Pliocene-Pleistocene volcanic rocks dredged here are similar to volcanites of the Kuril-Kamchatka Arc frontal zone.
Age and chemical composition of dredged igneous rocks from the Vityaz Ridge, Pacific slope of the Kuril Island Arc
Keywords: Akademik M.A. Lavrentyev; Archive of Ocean Data; ARCOD; Dredge; DRG; LV-37; LV-37-14; LV-37-17; LV-37-19; LV-37-22; LV-37-23; LV-37-24; LV-37-25; LV-37-37; Vityaz Ridge, Northwest Pacific